2007
DOI: 10.1037/0002-9432.77.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian mothers with planned families: A comparative study of internalized homophobia and social support.

Abstract: This study compared the perception of social support and the degree of internalized homophobia for two demographically similar groups: lesbians with planned families and lesbians who did not have children. Results found that lesbians with planned families perceived significantly less social support from friends overall, from gay men and lesbian friends specifically, and more support from their families-of-origin than lesbians who did not have children. Lesbians with planned families also reported significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 45 publications
2
35
0
4
Order By: Relevance
“…Although studies show that these women generally exhibit low levels of internalized homophobia (i.e., internalized stigma as a result of sexual orientation) (Baetens, 2002;HerrmannGreen & Gehring, 2007), a comparative study involving lesbian mothers and childless lesbian women found that mothers nonetheless scored higher with regard to internalized homophobia compared to those who were childless. Despite receiving more support from their family of origin, these mothers received less social support from their heterosexual and nonheterosexual friends (DeMino, Appleby, & Fisk, 2007). The extent to which women overcome the perceived conflict between a lesbian identity and motherhood plays an important role in the decision to start a family (Chabot & Ames, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Although studies show that these women generally exhibit low levels of internalized homophobia (i.e., internalized stigma as a result of sexual orientation) (Baetens, 2002;HerrmannGreen & Gehring, 2007), a comparative study involving lesbian mothers and childless lesbian women found that mothers nonetheless scored higher with regard to internalized homophobia compared to those who were childless. Despite receiving more support from their family of origin, these mothers received less social support from their heterosexual and nonheterosexual friends (DeMino, Appleby, & Fisk, 2007). The extent to which women overcome the perceived conflict between a lesbian identity and motherhood plays an important role in the decision to start a family (Chabot & Ames, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…At the same time a statement can be ventured that being a parent approaches LGB people to heterosexual majority, for whom parenting is a common practice. Quantitive research carried out in the United States exhibited mothers in planed lesbian families (N = 47) being higher supported by their families of origin and lower supported by their nonheterosexual friends in comparison with childless lesbians (N = 42) (DeMino, Appleby & Fisk, 2007). Qualitative study conducted in Italy (23 lesbians and 2 gay men) also suggests that LGB parents can expect more support from other heterosexual parents than from their own minority members (Danna, 2011).…”
Section: Lgb Parents As a Minoritymentioning
confidence: 94%
“…Because many lesbian mothers feel rejected by their families of origin, they often turn to chosen kin or social networks with some reporting high levels of social support from these networks (Donaldson, 2000;Rothblum, 2010). Yet research continues to find that, for others, social networks are sources of disconfirmation (DeMino, Appleby, & Fisk, 2007). Lack of social support from members of the lesbian and gay community is reported as a barrier to becoming a lesbian parent (Brown et al, 2009), and is theorized by some to result from dueling political opinions and goals in the lesbian community (Speziale & Gopalakrishna, 2004).…”
Section: The Origin Of Challenges For Families With Lesbian Mothersmentioning
confidence: 98%